2016
DOI: 10.1097/gme.0000000000000568
|View full text |Cite
|
Sign up to set email alerts
|

After-exercise heart rate variability is attenuated in postmenopausal women and unaffected by estrogen therapy

Abstract: Citation: HARVEY, P.J. ... et al., 2016. After-exercise heart rate variability is attenuated in postmenopausal women and unaffected by estrogen therapy. Menopause, 23 (4), pp. 390-395. ABSTRACT Objective: Delayed heart rate (HR) recovery in the immediate post-exercise period has been linked to adverse cardiovascular prognosis. The after-effects of an acute bout of exercise on HR modulation in postmenopausal women and the influence of estrogen therapy are unknown. Methods: In 13 sedentary postmenopausal women (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
3
9
2
Order By: Relevance
“…Therefore, the CRP and HRV values were analyzed with and without the participants who were on HT. Previous research from Harvey et al (2015) reported a lack of improvement in HRV following estrogen therapy 17 . Chi square was used to determine group differences for HT.…”
Section: Methodsmentioning
confidence: 92%
“…Therefore, the CRP and HRV values were analyzed with and without the participants who were on HT. Previous research from Harvey et al (2015) reported a lack of improvement in HRV following estrogen therapy 17 . Chi square was used to determine group differences for HT.…”
Section: Methodsmentioning
confidence: 92%
“…Studies have verified that aging and decreased estrogen levels are related to autonomic nervous changes of postmenopausal women [20], whereas some studies have not shown that estrogen therapy has a significant effect on heart rate variability (HRV) of postmenopausal women [21,22]. HRV is a simple and non-invasive tool for describing fluctuations between continuous heartbeat intervals (RR intervals) that can be used to identify phenomena associated with the autonomic nervous system [23].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, clinical studies have observed impaired autonomic modulation of the cardiovascular system by HRV in postmenopausal women when compared to premenopausal women [31][32][33]. It has been suggested that the reduced sympathetic tone in premenopausal women may contribute to help promote cardiovascular protection [34].…”
Section: Discussionmentioning
confidence: 99%